THE COMPARATIVE EFFICIENCY IN ROMANIA'S FOREIGN TRADE WITH CEREALS, 2007-2016 - Agatha POPESCU; Toma Adrian DINU; Elena STOIAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The purpose of the paper was to analyze Romania's foreign trade with cereals in order to point out its efficiency by type of traded cereal in the period 2007-2016 using the empirical data provided by the National Institute of Statistics. The study required a large variety of specific indicators and methods to reach its goal. In the period 2007-2016, both cereal export and import value increased, accounting for Euro 2,097.2 Million export and for Euro 591.1 Million import. As a result, Romania is a net exporting country of cereals as its trade balance was Euro 1,505.1 Million. Also, the volume of cereal trade increased by 5.36 times, reaching Euro 2,689.3 Million in 2016, the export per inhabitant increased reaching Euro 106.13/capita, and the coverage degree of import by export was 3.54 by 6 times higher than in 2007. In 2016, in the agro-food trade of Romania, cereals represented 35 % in the export value and 9 % in the import value. In 2016, the share of various cereals in the cereal export value accounted for: wheat 55.3 %, maize 34.4 % and barley 9.15 %, all together totalizing 98.85%, while the share of these cereals in cereal import value accounted for: wheat 56.9 %, maize 24.9 %, barley 11.9 % and rice 5.1 %, all together accounting for 98.8 %. In 2016, the trade balance for the main traded cereals was positive: wheat Euro 823.4 million, maize Euro 574.3 million, and barley Euro 121 million. The index of coverage degree of import by export was: 4.9 for maize, 3.4 for wheat, 3.1 for oats, 2.7 for barley, 1.9 for sorghum, 0.4 for rice and 0.3 for rye. The main trade partner for cereal export is the EU with a share of 30.7 %, the difference being represented by countries from the extra-EU market, and for import the EU had the top position with 95.8 % market share. The hierarchy of the cereals, in the decreasing order of the efficiency of their trade was the following one: wheat, barley, maize, rye, sorghum, oats and rice. But, the main cereals which deserve to be traded on external markets are wheat, maize and barley. This analysis has drawn the conclusion that Romania must commercialize more cereals with a high efficiency in foreign trade in terms of high export value, low import value, high positive trade balance and a high index of coverage degree of import by export. The positive trade balance had a good impact on the payment balance and on the economic growth.